REPLACING FUEL OIL BURNER IN A ZINC BATH KETTLE FOR GALVANIZATION PROCESS BY COAL CYCLONE ONE - SUMARYONO SUMARYONO (Puslitbang tekMIRA, 2006)
Most galvanizing industries use fuel oil to maintain a zinc bath temperature within the 440 – 455°C range. The oil burner is used in a heating chamber and the flue gas is then passed into the heating space under a zinc bath kettle at a temperature of 600°C. In this works one of the oil burner would be replaced by a coal burner. The kettle dimension is 12 x 1.5 x 1.8 m for its inner length, width and depth respectively. The heating space under the kettle is divided into two sections, each section is heated by a single oil burner of 50 - 80 litres/hour burning capacity. As there is no access into the heating space to remove the accumulated ash, the employed coal combustion technique should not transfer the ash into this chamber. For this purpose a vertical cyclone coal burner is used in a section with combustion capacity of 100 - 200 kg coal/hour. To minimize ash accumulation, a cyclone dust sepa- rator is connected after the cyclone burner, thus a cleaner flue gas enters the heating chamber. The coal used is a low ash sub-bituminous type of 5,500 kcal/kg at with particle sizes less than 30 mesh. Observation of temperature fluctuation in oil heated and coal heated sections during galvanization process showed that the fluctuation in both sections are in balance, indicating that the coal heating matches fuel oil heating in this system. The fuel used are 124 kg/hour for coal and 60 l/hour for fuel oil. To maintain zinc bath temperature around 430 – 455°C within 7 days galvanizing time operation it is found that fuel consumption is 20,300 kg of coal in the coal heated section and 10,080 l fuel oil in the oil heated section. It means that 1 l fuel oil is equivalent to 2 kg of coal or coal efficiency is 18.2% lower than the oil one in this system. The ash produced by the combustion of coal which trapped by both cyclones is 80% which is accumulated in the burner and 20% in the cyclone dust separator. The energy efficiency of coal is lower than that of the fuel oil since the use of fuel oil is directly burned within heating chamber, otherwise the coal is combusted in a cyclone burner and the flue gas enters the heating chamber after a longer journey through a cyclone dust separator.